CRISPR/Cas9-Mediated Targeting of SD1 Gene in Indonesian Local Varieties: Transformation and Preliminary Phenotypic Assessment of Semi-Dwarf Traits - Ubaidillah, Mohammad; Habibi, Ihsan; Gusti, Angger Aisyah Hadiahning; Aurela , Rosalina Diva; Hartatik, Sri; Hariyono, Kacung; Harmoko, Rikno (HAYATI Journal of Biosciences, 2026)
Indonesia boasts a wealth of local rice germplasm, with approximately 8,500 varieties recorded by IRRI, many of which feature adaptive traits and resistance to biotic and abiotic stresses. Nevertheless, it is likely limited by excessive plant height, which makes it sensitive to lodging. In contrast, the improved yields of modern semi-dwarf rice are twice those of older varieties, but are less resilient to local Indonesian stresses. This study focused on introducing semi-dwarf characteristics into two local varieties, Ketan Hitam and Pandan Wangi, via CRISPR/Cas9-mediated gene editing, which enables specific mutations and encodes the GA20-oxidase enzyme involved in gibberellin biosynthesis. A CRISPR/Cas9 construct (pRGEB32::SD1) carrying two sgRNAs targeting exon 1 and exon 2 was successfully designed and validated. Following Agrobacterium tumefaciens-mediated transformation and hygromycin selection. Ketan Hitam exhibited good survival, whereas Pandan Wangi depicted browning and poor regeneration. One regenerated Ketan Hitam T0 plantlet presented a preliminary semi-dwarf phenotype. PCR analysis verified the presence of the CRISPR/Cas9 construct. This study provides an initial demonstration of transformation probability and early phenotypic response in Ketan Hitam. Nevertheless, the phenotypic assay is based on a single T0 specimen, describing a key limitation of this study. The findings provide a basis for further multi-generational evaluation and agronomic improvement of Indonesian local rice.